Application of a Patient Safety Culture in Undata Palu Hospital - Freny Ravika Mbaloto; Niswa Salamung; Ni Ketut Elmiyanti (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: The Word Health Organization suggests that developed countries focus more on knowledge of standardized mechanisms and organizational factors that cause unsafe care for patients, such as those related to miscommunication, eg coordination, human error and the need to improve patient safety culture. Patient safety culture is a major and fundamental factor because building a patient safety culture is a way to build an overall patient safety program. This study aims to determine the applicationof patients safety culture at  Undata Hospital, Palu, Central Sulawesi Province, Indonesia.  Method: Using a survey questionnaire, this study explores differences in the application of of patient safety cultures in patient, critical and emergency rooms. The research samples of 157 people obtained through the use of probability sampling techniques. Data were analyzed using Fisher's exact test. The statistic show that there are differences in the application of safety culture in patient, critical and emergency rooms. Because there are differences in the application of safety culture between rooms, the statistical analysis was continued with the Post Hoc Mann-Whitney test. Results: The results showed that statistically there was no difference in the application of patient safety culture between inpatient and critical rooms because p = 0.643 (p> 0,05 ), a difference in the application of patient safety culture between in patient and emergency rooms because p = 0.011 (p <0,05), a difference in the application of patient safety culture between critical rooms and emergency rooms because p = 0.049 (p<0.05).